Phosphorylation of Kindlins and the Control of Integrin Function - Bialkowska, Katarzyna (Cells, 2021)
Integrins serve as conduits for the transmission of information between cells and their extracellular environment. Signaling across integrins is bidirectional, transducing both inside-out and outside-signaling. Integrin activation, a transition from a low affinity/avidity state to a high affinity/avidity state for cognate ligands, is an outcome of inside-signaling. Such activation is particularly important for the recognition of soluble ligands by blood cells but also influences cell-cell and cell-matrix interactions. Integrin activation depends on a complex series of interactions, which both accelerate and inhibit their interconversion from the low to the high affinity/avidity state. There are three components regarded as being most proximately involved in integrin activation: the integrin cytoplasmic tails, talins and kindlins. The participation of each of these molecules in integrin activation is highly regulated by post-translation modifications. The importance of targeted phosphorylation of integrin cytoplasmic tails and talins in integrin activation is well-established, but much less is known about the role of post-translational modification of kindlins. The kindlins, a three-member family of 4.1-ezrin-radixin-moesin (FERM)-domain proteins in mammals, bind directly to the cytoplasmic tails of integrin beta subunits. This commentary provides a synopsis of the emerging evidence for the role of kindlin phosphorylation in integrin regulation.